Significant of Business Intelligence (BI) in Customer Retention: Nigerian GSM Industry - Olukayode, Popoola (2009)
The telecommunication carrier’s critical success factor has for a long time depended on the core competencies of the technical expertise for continuous product innovations, aimed at attracting and retaining customer (Kawashima, 2002). However, with the dynamic changes in the sector, emergency of network convergence, evident in the wireless sector and the deployment of the broadband network, a paradigm shifts in business model is inevitable. And according to the Harvard Business Review. “Competence now is a function of the collective knowledge available to the whole system.” (Prahalad and Ramaswamy, 2001) Therefore, the value proposition for a Telco is shifting from just operational efficiency to incorporate customer as a source of competence, this making the delivery of high value customer’s service imperative and a differentiator in the highly competitive market. “Telecommunications companies are increasingly turning to customer analysis to maintain their competitive advantage.” (Microstrategy, 2002) Moreover, the acceptability of the web as a medium for transaction is gradually gaining the attention of telcos as a veritable tool, for enhancing customer service. According to Chau (2007), the employment of self service techniques in enabling customer to optimize the control of information and resources, is a cost effective approach, which can be deployed by Telcos to improve the experience of an average customer. This paper is focused on evaluating the customer retention strategy of wireless telcos in Nigeria; with a view to recommend the business intelligence based solution.